Pemanfaatan Ampas Tahu Menjadi Jajanan Kekinian Sebagai Usaha Untuk Pemanfatan Limbah Ampas Tahu Di Kelurahan Lewirato - Ismunandar Ismunandar; Mulyadin Mulyadin; Lewirato Lewirato (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Despite being rich in protein, fat, and water content, the utilization of tofu dregs remains limited, with entrepreneurs predominantly using it as animal feed, material for making "gembos" tempe, and crackers, which have not significantly contributed to the community's economic welfare. In the Lewirato district, tofu dregs are solely utilized as cattle feed, although its potential to be processed into value-added food products remains largely untapped. Therefore, the objective of this community service initiative is to provide training to the locals on how to process tofu dregs into products such as sponge cakes, okara sticks, and tofu dregs bread with improved packaging and branding. The implementation method encompasses initial surveys, program socialization, training sessions, and evaluation, with the aim of empowering the community to optimize the utilization of tofu dregs as trendy snacks that offer economic value addition.